Performance Contracts and Service Delivery in Rural Local Authorities: A Myth or a Reality - Farai Ncube; Thamsanqa Donga; Cynthia Gauya (Globeedu Group, 2023)
Rural local authorities in Zimbabwe have been facing serious service delivery challenges which prompted the government to introduce performance contracts for management across the 92 local authorities throughout the country. In essence performance contracts can be used as a management tool to create accountability to the public for harnessing targeted results. The study sought to determine the reality of the contracts as a measure to harness service delivery challenges. The study adopted a case study approach of Umguza rural local authority. A sample of 50 participants was used, with data having been collected through the use of questionnaires and interviews. From these 50 respondents 30 were on performance contracts while 20 were non-managerial employees who were internal customers that knowledge of service delivery challenges. Results obtained indicated a stride towards enhanced service delivery through performance contracts albeit serious challenges threatening their effectiveness.